The General Iterative Methods for Asymptotically Nonexpansive Semigroups in Banach Spaces - Rabian Wangkeeree; Pakkapon Preechasilp (Abstract and Applied Analysis)
We introduce the general iterative methods for finding a common fixed point of asymptotically nonexpansive semigroups which is a unique solution of some variational inequalities. We prove the strong convergence theorems of such iterative scheme in a reflexive Banach space which admits a weakly continuous duality mapping. The main result extends various results existing in the current literature.